The effect of apixaban on the pharmacokinetics of digoxin and atenolol in healthy subjects - Frost C; Song Y; Yu Z; Wang J; Lee LS; Schuster A; Pollack A; LaCreta F (Dove Medical Press, 2017)
Charles Frost,1 Yan Song,1 Zhigang Yu,2 Jessie Wang,3 Lois S Lee,4 Alan Schuster,5 Allyson Pollack,1 Frank LaCreta1 1Exploratory Clinical and Translational Research, Bristol-Myers Squibb, Princeton, NJ, USA; 2Medical Sciences, Amgen Asia R&D Center, Shanghai, People’s Republic of China; 3Global Biometric Sciences, Bristol-Myers Squibb, Princeton, NJ, 4Clinical Research, Intercept Pharmaceuticals, San Diego, CA, 5Bioanalytical Sciences, Bristol-Myers Squibb, Princeton, NJ, USA Purpose: Apixaban is often coadministered with treatments for cardiovascular comorbidities, which may lead to unintended drug−drug interactions (DDIs). The effects of apixaban on pharmacokinetics (PK) of multidose Lanoxin® (digoxin) and single-dose Tenormin® (atenolol) and the effects of single-dose atenolol on apixaban PK in healthy subjects were investigated in two Phase 1 studies. Patients and methods: The digoxin DDI study was an open-label, multidose, two-treatment, single-sequence study in which subjects received digoxin 0.25 mg q6h on day 1, then once daily on days 2–10, followed by apixaban 20 mg and digoxin 0.25 mg once daily on days 11–20. The atenolol DDI study was an open-label, single-dose, randomized, three-period, three-treatment, crossover study in which subjects received a single oral dose of apixaban 10 mg, atenolol 100 mg, or apixaban 10 mg plus atenolol 100 mg. The 90% confidence intervals (CIs) for the ratios of geometric means of peak plasma concentration (Cmax) and area under the concentration–time curve (AUCtau), with and without apixaban were calculated. Absence of effect was concluded if the point estimates and 90% CI were within the equivalence interval of 80%–125% (digoxin) or 70%–143% (atenolol). A similar analysis was performed to assess the effect of atenolol on apixaban. Results: Apixaban had no clinically relevant effect on the PK of either atenolol or digoxin: point estimates and 90% CI for both digoxin and atenolol Cmax and AUC were entirely within their respective no-effect intervals. Apixaban Cmax and AUCinf were slightly decreased (ie, 18% and 15% lower, respectively) following atenolol coadministration. No serious or major bleeding-related adverse events were reported during either study. Conclusion: Apixaban had no effect on the PK of digoxin and there was no clinically relevant interaction between apixaban and atenolol. Coadministration of digoxin or atenolol with apixaban in healthy subjects was generally well tolerated. Keywords: oral anticoagulant, factor Xa inhibitor, drug–drug interaction, Phase 1